2015
DOI: 10.1002/celc.201500325
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Formation and Phase Control of Mg–Cu Alloys

Abstract: Mg–Cu alloys with different phases were electrodeposited in a molten LiCl–KCl eutectic mixture containing a small amount (0.5 mol %) of MgCl2 at 673 K. The electrochemical behavior of the MgII ion and alloy formation processes were studied at inert molybdenum (Mo) and active copper (Cu) electrodes in the molten salts, respectively. Different electrochemical techniques, such as cyclic voltammetry, square‐wave voltammetry, chronoamperometry, and open‐circuit potentiometry were carried out to investigate the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…1 , B 1 /B 1 and C 1 / C 1 in solid line (obtained with SiC fiber/Cu electrode) should be in accordance with these redox peaks of A 2 /A 2 , B 2 /B 2 and C 2 / C 2 in dashed line (obtained with Cu wire electrode), respectively. These three redox peaks should be corresponding to the deposition and dissolution of the alloys MgCu 2 , Mg 2 Cu and Mg, respectively, according to our former work 20. This experiment indicated that SiC/Cu electrode showed almost the same properties of metal Cu electrode in the electrodeposition processes.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…1 , B 1 /B 1 and C 1 / C 1 in solid line (obtained with SiC fiber/Cu electrode) should be in accordance with these redox peaks of A 2 /A 2 , B 2 /B 2 and C 2 / C 2 in dashed line (obtained with Cu wire electrode), respectively. These three redox peaks should be corresponding to the deposition and dissolution of the alloys MgCu 2 , Mg 2 Cu and Mg, respectively, according to our former work 20. This experiment indicated that SiC/Cu electrode showed almost the same properties of metal Cu electrode in the electrodeposition processes.…”
supporting
confidence: 68%
“…Electrochemical equipment and techniques.-The molten salt electrodeposition experiments were carried out in an apparatus described in detail in our previous works. 20 The dried LiCl-KCl-MgCl 2 mixture was placed in a high-purity alumina crucible, which was then held in a stainless steel cylindrical cell in an electric furnace. Electrochemical measurements were carried out in the three-electrode configuration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the relationship of electric quantity (Q) and the square root of time (t 1/2 ) is linear, the electrode reaction is controlled by diffusion of ions to electrode surface. 52 Thus, it demonstrates from Fig. 7b that the reaction of Y(III) on liquid Pb electrode is controlled by diffusion.…”
Section: Electrochemical Reaction Of Y(iii) On Liquid Pb Electrodementioning
confidence: 80%
“…13d ) shows the sample is mainly composed of two phases, Pb and Pb 3 Y. According to Pb–Y phase diagram, 52 there are four Pb–Y intermetallic compounds (Pb 3 Y, Pb 2 Y, Pb 4 Y 5 and Pb 3 Y 5 ). When the extraction was performed on liquid Pb electrode, the amount of Pb is large, thus, the Pb-richest Pb–Y compound Pb 3 Y can be formed.…”
Section: Resultsmentioning
confidence: 99%